AN ANALYSIS OF INTERLANGUAGE PERFORMED BY STUDENTS OF AN ISLAMIC BOARDING SCHOOL IN TASIKMALAYA - Aziez, Feisal (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2016)
Abstract This descriptive study aims at: (1) finding out and describe the phonological, lexical, and syntactic forms of English language learnersâ inter language, and (2) finding out whether there are any differences in the inter language of the learners of different grades. The subjects of this research were 24 learners of the first, second, and third grade of an Islamic boarding school in Tasikmalaya. The data were collected from studentsâ conversations, interviews, and reading aloud. The data were recorded and transcribed. Then, the data were filtered by using Corderâs procedure. The results of the research reveal the existence of the following aspects in the learnersâ inter language: (1) phonological transfers, (2) lexical transfers, (3) syntactic transfers, (4) phonological overgeneralizations, (5) lexical overgeneralizations, and (6) syntactic overgeneralizations. This research also found out some differences in the inter language of the students of different grades. Keywords: inter language, pesantren, phonological, lexical, syntactic, language transfers, overgeneralizations